2007
DOI: 10.1038/sj.ijo.0803535
|View full text |Cite
|
Sign up to set email alerts
|

Plasma leptin levels are related to body composition, sex, insulin levels and the A55V polymorphism of the UCP2 gene

Abstract: Objective: Circulating leptin levels show a high degree of individual variability even after the main effect of body fatness is accounted for. We therefore wanted to determine the roles of variation in body composition, age, sex and polymorphisms of the UCP2 gene and promoter region on levels of circulating leptin. Subjects: One hundred and fifty Caucasian subjects, which represented a cross-section of the population from NE, Scotland, were recruited. Measurements: Body composition was measured using dual X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…O'Rourke et al [50] demonstrated that Leptin significantly increased LIPE activity in human J774.2 macrophages. Rance et al [51] found an association between human leptin and A55V of the UCP2 gene (−866G>A and exon-8 ins/del) (P<0.01), so they suggested that the A55V polymorphism directly affected the levels of leptin. There were great discrepancies between the GRNs of the two pig breeds, an observation which hypothetically reveals the dissimilar molecular basis for adipose metabolism in lean Landrace versus fatty Taihu pigs.…”
Section: Discussionmentioning
confidence: 96%
“…O'Rourke et al [50] demonstrated that Leptin significantly increased LIPE activity in human J774.2 macrophages. Rance et al [51] found an association between human leptin and A55V of the UCP2 gene (−866G>A and exon-8 ins/del) (P<0.01), so they suggested that the A55V polymorphism directly affected the levels of leptin. There were great discrepancies between the GRNs of the two pig breeds, an observation which hypothetically reveals the dissimilar molecular basis for adipose metabolism in lean Landrace versus fatty Taihu pigs.…”
Section: Discussionmentioning
confidence: 96%
“…16,17 In this regard, other genetic polymorphisms have been associated with obesity, including the dopamine D2 receptor (DRD2), methylenetetrahydrofolate reductase (MTHFR), leptin (LEP), serotonergic receptor (5-HT2A), and peroxisome proliferator-activated receptor gamma 2 (PPAR-γ2) genes. [18][19][20][21][22][23] Serotonin Figure 1. Brain reward cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Several UCP2 gene variants have been reported in human studies and include: a G/A single nucleotide polymorphism (SNP) in the promoter region (-866G/A) [23], a valine-for-alanine substitution at amino acid 55 in exon 4 (Ala55Val), and a 45-bp insertion/deletion in the 3 0 -untranslated region [24,25]. The Ala55Val polymorphism has been linked to variations in the energy balance via effects on the RMR and nocturnal physical activity [26,27], and to type 2 diabetes [28,29].…”
Section: Introductionmentioning
confidence: 99%